2020
DOI: 10.3390/ijerph17176051
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Trace Elements and Cognitive Decline: An Exploratory 5-Year Follow-Up Study of an Elderly Cohort

Abstract: Trace elements (TE) homeostasis is crucial in normal brain functioning. Although imbalances have the potential to exacerbate events leading neurodegenerative diseases, few studies have directly addressed the eventual relationships between TE levels in the human body and future cognitive status. The present study aimed to assess how different TE body-levels relate to cognitive decline. This exploratory research included a study-group (RES) of 20 elderly individuals living in two Portuguese geographical areas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…PAHs are bound to release into the atmosphere mainly in the vapor phases directly arising from the combustion facility. PAHs could also be released along with the solid phases (CFA or bed ash), from where they could be either evaporated or dissipated into the surrounding environment [51]. The PAH percentage in CFA mainly depends on the type of coal or fuel used, the technology applied for the burning of coal, and the residence time of ash inside the combustion facility [52].…”
Section: Coal Fly Ash As a Source Materials Of Pahsmentioning
confidence: 99%
“…PAHs are bound to release into the atmosphere mainly in the vapor phases directly arising from the combustion facility. PAHs could also be released along with the solid phases (CFA or bed ash), from where they could be either evaporated or dissipated into the surrounding environment [51]. The PAH percentage in CFA mainly depends on the type of coal or fuel used, the technology applied for the burning of coal, and the residence time of ash inside the combustion facility [52].…”
Section: Coal Fly Ash As a Source Materials Of Pahsmentioning
confidence: 99%
“…In addition, several metabolic and physiological pathways, including excretion function are known to be altered during the aging process, contributing to an accumulation of micronutrients such as Se. Yet, this “improved” Se profile has been shown to have a beneficial effect on aging and age-related manifestations [ 41 , 49 , 50 ]. Although a negative association or even no association between Se intake and metabolic syndrome has been reported [ 51 ], the risk of developing this cluster of disorders may increase in people with elevated Se levels [ 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Hippocampus on warming and tonifying kidney yang also benefited from mineral elements (Zhang et al, 1997). Clinical studies have shown that higher levels of mineral elements may reduce the likelihood of declines in cognitive function over 5 years (Gerardo et al, 2020). In the brain, various nervous activities require the participation of essential mineral elements, such as Fe and Zn.…”
Section: Mineral Elementsmentioning
confidence: 99%